Contact force exerted on the maxillary incisors by direct laryngoscopy with mcgrath video laryngoscope in predicted difficult intubation - Doddy Setiawan; Tjokorda Gde Agung Senapathi; I Gede Budiarta; I Gusti Ngurah Mahaalit Aribawa (Indoscholar, 2021)
Patients with difficult airways who are going to undergo surgery under general anesthesia require special consideration from an anesthesiologist. Knowing the most significant risk of morbidity and mortality is often due to difficult cases of airway management. One of the most common complications and often becomes lawsuits in the field of anesthesia is dental trauma that occurs during the intubation process due to contact from laryngoscope blade to the teeth. This descriptive study will show the measured force exerted on the maxillary incisors at the time of performing laryngoscopy using a McGrath video laryngoscope in patients with a potentially difficult intubation (LEMON criteria ≥ 3). The contact force exerted on the maxillary incisors is measured using a special instrument. The contact force exerted on the maxillary incisors in patients with a potentially problematic airway was discovered to vary.